2015
DOI: 10.5007/1980-0037.2015v17n6p733
|View full text |Cite
|
Sign up to set email alerts
|

O efeito do “FIFA 11+” na performance de saltos verticais em atletas de futebol

Abstract: -The aim of this study was to evaluate the effect of 9 weeks of the "FIFA 11+" warm-up program on vertical jump performance in soccer players. The study included 20 athletes of the Under-20 category from a Brazilian championship serie A team (age: 18.3±1.6 years; years of training: 8.2±1.3; body weight: 74.0±7.1 kg, height: 177.8±6.5 cm, and fat percentage: 10.7±1.9%), divided into an intervention group (G11+; n=10) and a control group (CG; n=10). The athletes were evaluated before and after the intervention r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
1
2
0
1
Order By: Relevance
“…The results showed that eight weeks of FIFA 11+ training had a significant effect on improving vertical jump and long jump in young volleyball players. Consistent with the findings of the present study, Ayala et al (14), Akbari et al (15), and Costa Silva et al (17) reported that FIFA 11+ training improved vertical jump in young male soccer players. Fazl Ersi et al (12) showed that strengthening the central stability of the body was effective in transmitting power in high jump motion.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results showed that eight weeks of FIFA 11+ training had a significant effect on improving vertical jump and long jump in young volleyball players. Consistent with the findings of the present study, Ayala et al (14), Akbari et al (15), and Costa Silva et al (17) reported that FIFA 11+ training improved vertical jump in young male soccer players. Fazl Ersi et al (12) showed that strengthening the central stability of the body was effective in transmitting power in high jump motion.…”
Section: Discussionsupporting
confidence: 92%
“…FIFA 11+ training improved the speed, jump, and stability of young amateur soccer players (14). Also, eight weeks (15), four weeks (16), and nine weeks (17) of the FIFA 11+ training resulted in improved jump height in young soccer players (15). However, contrary to the above results, some studies indicated the ineffectiveness of FIFA 11+ injury prevention program in promoting athletes' performance.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…El programa de calentamiento Fifa 11+ fue desarrollado por el Centro Médico de Evaluación e Investigación de la Fifa (f-marc, por sus siglas en inglés), a través de ejercicios dinámicos y específicos (Costa, Fernandes, Salvador y Rocha 2015), compuesto por entrenamiento pliométrico, balance y agilidad (Nakase et al, 2013). Este material se encuentra disponible en inglés, alemán, francés, italiano y español (Junge et al, 2010).…”
Section: Introductionunclassified